Implication of stem cells and platelet rich plasma in otolaryngology, head and neck surgical procedures - Muhammad Fazal Hussain Qureshi; Soubia Akhtar; Shayan Khalid Ghaloo; Muhammad Wasif; Hamdan Ahmed Pasha; Rahim Dhanani (Journal of the Pakistan Medical Association, 2023)
Human body has a set of unspecialized cells called as stem cells that have the ability to generate cells of specialized function. Volume of fractionated plasma extracted from autologous blood is termed as Platelet-rich plasma (PRP) that is rich in several growth factors. Both have shown effective results in the field of regenerative medicine. Physiologically, platelets are the first cells to concentrate at the site of tissue damage, therefore application of PRP in diverse surgical procedures enhances bone and soft tissue healing; this same phenomenon is currently being used in otology, head and neck flap surgery and yielding miraculous outcomes. The perspective role of stem cells in regenerative medicine is wrapped in its loosely arranged DNA with working genes; a similar concept is being worked upon in different ENT procedures with groundbreaking results. Continued...